2017
DOI: 10.1007/s11695-017-2867-3
|View full text |Cite
|
Sign up to set email alerts
|

Is Concomitant Cholecystectomy Necessary for Asymptomatic Cholelithiasis During Laparoscopic Sleeve Gastrectomy?

Abstract: The risk of becoming symptomatic for asymptomatic cholelithiasis is very close to the healthy population after sleeve gastrectomy. Although further studies with a high number of cases are needed, we suggest only observation for asymptomatic gallbladder stones in patients who will undergo sleeve gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…However, a lack of consensus remains on this topic. A recent study found that the risk of developing cholelithiasis after LSG in asymptomatic patients is close to the healthy population, recommending observation only in such cases (33). Another method for preventing cholelithiasis is by prescribing ursodeoxycholic acid as prophylaxis for the first 6 months post-operatively, yet there is insufficient evidence to support its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lack of consensus remains on this topic. A recent study found that the risk of developing cholelithiasis after LSG in asymptomatic patients is close to the healthy population, recommending observation only in such cases (33). Another method for preventing cholelithiasis is by prescribing ursodeoxycholic acid as prophylaxis for the first 6 months post-operatively, yet there is insufficient evidence to support its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid weight loss after bariatric surgery is regarded as responsible for the formation of cholelithiasis. [13] The incidence of symptomatic gallstones requiring cholecystectomy after laparoscopic sleeve gastrectomy (LSG) was reported as 0.9-7.5% in the literature. [13] In follow-ups of the 1268 cases operated in this study, symptomatic cholelithiasis was detected in 6 cases (0.47%).…”
Section: Discussionmentioning
confidence: 99%
“…e follow-up period is longer in Yardimci et al's study so that they could observe that 20.8% of the patients with asymptomatic GS became symptomatic in the 27-month follow-up period. ey believed that the ratio of LC requirement may be higher as the follow-up time lengthens [4]. Some surgeons reported that complications increased during LSG resulting from adding LC: Dakour-Aridi et al studied 21,137 patients who underwent LSG and were reported in NSQIP, of whom 2.0% underwent concomitant LC.…”
Section: Scott Et Al Reported That An Advantage Of Delayed Lc Ismentioning
confidence: 99%
“…On the other hand, adding concomitant LC to a BS poses certain risks due to the increased morbidity for patients with obesity, and it may be technically challenging due to excess intra-abdominal fat and difference in ports' placement for BS and LC with difficulties establishing and maintaining pneumoperitoneum, the higher incidence for conversion to open surgery and bile duct injuries [2,3]. e time interval allows LC to be performed more safely due to loss of intra-abdominal fat and the possible late complications of BS; for example, port site hernia can be operated on simultaneously [4]. erefore, the surgeon has to weigh the potential added risk of concomitant LC with the potential morbidity of delayed complications from GS [5].…”
Section: Introductionmentioning
confidence: 99%